2016
DOI: 10.1371/journal.pone.0168433
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Staphylococcus aureus Isolates in European Wildlife

Abstract: Staphylococcus aureus is a well-known colonizer and cause of infection among animals and it has been described from numerous domestic and wild animal species. The aim of the present study was to investigate the molecular epidemiology of S. aureus in a convenience sample of European wildlife and to review what previously has been observed in the subject field. 124 S. aureus isolates were collected from wildlife in Germany, Austria and Sweden; they were characterized by DNA microarray hybridization and, for isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 157 publications
(246 reference statements)
4
109
2
1
Order By: Relevance
“…The mecA-positive strain was isolated from the nasal sample of a European hedgehog. MRSA have already been detected in this animal species (Monecke et al 2013;Monecke et al 2016), but in those cases, the methicillin-resistance determinant was mecC. Our MRSA-mecA strain was typed as t386-ST1/CC1-SCCmecIVa-agrIII.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The mecA-positive strain was isolated from the nasal sample of a European hedgehog. MRSA have already been detected in this animal species (Monecke et al 2013;Monecke et al 2016), but in those cases, the methicillin-resistance determinant was mecC. Our MRSA-mecA strain was typed as t386-ST1/CC1-SCCmecIVa-agrIII.…”
Section: Discussionmentioning
confidence: 71%
“…The blaZ allotype within the SCCmec-XI that harbour the mecC isolates, presents a 67% amino acid identity with the previously known blaZ gene of S. aureus (Shore et al 2011), and have been demonstrated its penicillinase activity (G omez et al, 2014). The mecC gene has been previously detected in farmed rabbits from Belgium from a case of highly virulent cutaneous infection in 1995 (Devriese et al 1996;Paterson et al 2012), and in brown hares in Germany (Monecke et al 2016). Originally, the CC130 was associated to MSSA, but in recent years it is being of particular concern due to its relationship with the mecC gene.…”
Section: Discussionmentioning
confidence: 99%
“…; Monecke et al . ). This is the case of MRSA transmitted from swines to human and the isolation of penicillin, lincomycin, erythromycin, pristinamycin, kanamycin and pefloxacin‐resistant strains (Cuny et al .…”
Section: Resultsmentioning
confidence: 97%
“…Some studies have demonstrated the transmission of multidrug-resistant pathogens between species, including human (Marshall et al 2009). The emergence of methicillin-resistant S. aureus (MRSA) becomes a worldwide public health problem, with resistant strains being isolated from humans and a variety of animal species, such as horses, pet animals, livestock and wildlife (Wardyn et al 2012;Patersen et al 2014;Monecke et al 2016). This is the case of MRSA transmitted from swines to human and the isolation of penicillin, lincomycin, erythromycin, pristinamycin, kanamycin and pefloxacinresistant strains (Cuny et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…rather than exact species types) but demonstrates some sharing of spa types between humans, domestic animals, and wildlife (more for the former than the latter). Yellow-necked mouse t208/ST49, t4189/ST49, t1773/ST890, t843/ST130 ND Germany [42] House mouse t843/ST130 ND Germany [42] Bank vole t208/ST49, t4189/ST49 ND Germany [42] Bank vole (Myodes glareolus) CC49, ST890, ST1959 MSSA Germany [40] Common vole t1773/ST890, t15027/ST3252, t3058/ST3252, t3830/ST1956 ND Germany, Czech Republic [42] Field vole t1736/ST890, t2311/ST88, t3830/ST1956 ND Germany [42]…”
Section: Full-text Articles Excludedmentioning
confidence: 99%